Patient-Ventilator Interaction During Noninvasive Ventilation in Subjects With Exacerbation of COPD: Effect of Support Level and Ventilator Mode. - Oppersma, Eline; Doorduin, Jonne; Roesthuis, Lisanne H.; van der Hoeven, Johannes G.; Veltink, Peter H.; Heunks, Leo M. A. (Respiratory Care, 2020)
BACKGROUND: Patient-ventilator synchrony in patients with COPD is at risk during noninvasive ventilation (NIV). NIV in neurally-adjusted ventilatory assist (NAVA) mode improves synchrony compared to pressure support ventilation (PSV). The current study investigated patient-ventilator interaction at 2 levels of NAVA and PSV mode in subjects with COPD exacerbation. METHODS: NIV was randomly applied at 2 levels (5 and 15 cm H2O) of PSV and NAVA. Patient-ventilator interaction was evaluated by comparing airway pressure and electrical activity of the diaphragm waveforms with automated computer algorithms. RESULTS: 8 subjects were included. Trigger delay was longer in PSV high (268 ± 112 ms) than in PSV low (161 ± 118 ms, P = .043), and trigger delay during NAVA was shorter than PSV for both low support (49 ± 24 ms for NAVA, P = .035) and high support (79 ± 276 ms for NAVA, P = .003). No difference in cycling error for low and high levels of PSV (PSV low -100 ± 114 ms and PSV high 56 ± 315 ms) or NAVA (NAVA low -5 ± 18 ms, NAVA high 12 ± 36 ms) and no difference between PSV and NAVA was found. CONCLUSIONS: Increasing PSV levels during NIV caused a progressive mismatch between neural effort and pneumatic timing. Patient-ventilator interaction during NAVA was more synchronous than during PSV, independent of inspiratory support level. (ClinicalTrials.gov registration NCT01791335.).